2018
DOI: 10.1080/19396368.2018.1515272
|View full text |Cite
|
Sign up to set email alerts
|

Research advances in the regulation of the putative ovarian germline stem cell niche on female germline stem cells

Abstract: BMP: bone morphogenetic protein; Dpp: decapentaplegic; FGSC: female germline stem cell; IL, interleukin; OGSC: ovarian germline stem cells; ROS: reactive oxygen species; TGF, transforming growth factor; TNF, tumor necrosis factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…In consideration of that FGSCs niche structure and function in mammals are less clear than that of drosophila, we believe that the mammal niche is similar to the drosophila niche. The niche of ovaries in mammals maybe includes follicular membrane-stromal cells, granulosa cells, extracellular matrix, blood vessels, immune system-related cells and cytokines [ 55 ]. Bukovsky observed that niche of FGSCs formed during early embryonic development consist of nonspecific ovarian monocyte-derived cells(MDCs), T cells, and vascular endothelial cells, whereas nests of adult ovarian germinal stem cells consist of primary CD14 + MDCs, activated HLA-DR + MDCs and T cells [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of that FGSCs niche structure and function in mammals are less clear than that of drosophila, we believe that the mammal niche is similar to the drosophila niche. The niche of ovaries in mammals maybe includes follicular membrane-stromal cells, granulosa cells, extracellular matrix, blood vessels, immune system-related cells and cytokines [ 55 ]. Bukovsky observed that niche of FGSCs formed during early embryonic development consist of nonspecific ovarian monocyte-derived cells(MDCs), T cells, and vascular endothelial cells, whereas nests of adult ovarian germinal stem cells consist of primary CD14 + MDCs, activated HLA-DR + MDCs and T cells [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Female germline stem cells (FGSCs) maintain the female reproductive functions and FGSCs have been extensively studied during the stages of oogenesis. 16 The ability to isolate FGSCs and study their proliferation enables the understanding of neo-oogenesis and ovarian recession. 17 This current study explored whether SHK controls the proliferation, differentiation and apoptosis of FGSCs.…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition, oxidative stress impairs the stem-cell niche and induces follicular atresia. 16 , 17 The bioactivity of superoxide dismutase (SOD) and glutathione (GSH) counteracts the oxidative cytotoxicity induced by reactive oxygen species (ROS). 1619…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations